Perancangan User Interface Pada Aplikasi Lapor Menggunakan Knowledge Management - Muhammad Chandra Prawira; Ken Dhita Tania (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
School is an educational institution that organizes the teaching and learning process. School activities for teachers and students also depend on good learning, collection and management of knowledge. Because the teacher is one of the key success factors for any educational endeavor, teachers are therefore expected to act as educators, instructors, and mentors to improve student learning outcomes and motivate students to learn. The role of a teacher is very influential in realizing the quality of education, especially teacher performance. Therefore, teacher performance is one of the most important conditions for successful learning. SMP Negeri 60 Palembang has problems handling student and teacher cases and this school is also a new school where there are constraints on inadequate and incomplete facilities with a large number of students, causing the teaching and learning process to be slightly hampered. The design thinking method can understand users, present evidence, and overcome problems in devising strategies to find solutions. Therefore, design thinking is considered capable of solving problems in creating solutions based on user needs. To support the process of information purposes at SMPN 60 Palembang without being limited by distance and time so that the information can be used optimally by both students and teachers.